2009
DOI: 10.1007/s10549-009-0588-6
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of breast cancer related gene expression using natural splines and the Cox proportional hazard model to identify prognostic associations

Abstract: Many studies correlating gene expression data to clinical parameters assume a linear increase or decrease of the clinical parameter under investigation with the expression of a gene. We have studied genes encoding important breast cancer-related proteins using a model for survival-type data that is based on natural splines and the Cox proportional hazard model, thereby removing the linearity assumption. Expression data of 16 genes were studied in relation to metastasis-free probability in a cohort of 295 conse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 34 publications
1
22
0
Order By: Relevance
“…RNA of sufficient quantity and quality was available for 48 cases and the gene expression profiles were reported in Natrajan et al [29]. Immunohistochemistry for ER, progesterone receptor (PR) and HER2 was performed as previously described [9,31]. Histological grade was determined by two pathologists (FCG and JSR-F) using the modified Scarff-Bloom-Richardson system [32].…”
Section: Methodsmentioning
confidence: 99%
“…RNA of sufficient quantity and quality was available for 48 cases and the gene expression profiles were reported in Natrajan et al [29]. Immunohistochemistry for ER, progesterone receptor (PR) and HER2 was performed as previously described [9,31]. Histological grade was determined by two pathologists (FCG and JSR-F) using the modified Scarff-Bloom-Richardson system [32].…”
Section: Methodsmentioning
confidence: 99%
“…Most of these studies have used immunohistochemical expression of the cyclin D1 expression [7, 10, 12, 13, 1622, 25, 26, 28, 29, 3142, 44, 45, 47–49], some mRNA expression [5, 23, 29, 30, 46], some amplification of the CCND1 gene [10, 11, 13, 14, 16, 24, 27, 43], and several methods [10, 13, 16, 29]. There is still no consensus about which method of assessment of cyclin D1 signaling aberrations is optimal.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, a few more recent methods allow the user to simultaneously account for the violations of both assumptions in a single model . Applications of these flexible models demonstrated that many risk/prognostic factors investigated in epidemiological and clinical research have nonlinear or time‐dependent (i.e., non‐PH) effects . Furthermore, for some continuous covariates, both the linearity and PH assumptions may be violated .…”
Section: Introductionmentioning
confidence: 99%